The association of socioeconomic status with Hypertension in 76 low- and middle-income countries - Kirschbaum, Tabea K.; Sudharsanan, Nikkil; Manne-Goehler, Jennifer; De Neve, Jan-Walter; Lemp, Julia M.; Theilmann, Michaela; Marcus, Maja E.; Ebert, Cara; Chen, Simiao; Yoosefi, Moein; Sibai, Abla M.; Rouhifard, Mahtab; et al. (Journal of the American College of Cardiology, 2022)
Background - Effective equity-focused health policy for hypertension in low- and middle-income countries (LMICs) requires an understanding of the condition’s current socioeconomic gradients and how these are likely to change in the future as countries develop economically. - Objectives - This cross-sectional study aimed to determine how hypertension prevalence in LMICs varies by individuals’ education and household wealth, and how these socioeconomic gradients in hypertension prevalence are associated with a country’s gross domestic product (GDP) per capita. - Methods - We pooled nationally representative household survey data from 76 LMICs. We disaggregated hypertension prevalence by education and household wealth quintile, and used regression analyses to adjust for age and sex. - Results - We included 1,211,386 participants in the analysis. Pooling across all countries, hypertension prevalence tended to be similar between education groups and household wealth quintiles. The only world region with a clear positive association of hypertension with education or household wealth quintile was Southeast Asia. Countries with a lower GDP per capita had, on average, a more positive association of hypertension with education and household wealth quintile than countries with a higher GDP per capita, especially in rural areas and among men. - Conclusions - Differences in hypertension prevalence between socioeconomic groups were generally small, with even the least educated and least wealthy groups having a substantial hypertension prevalence. Our cross-sectional interaction analyses of GDP per capita with the socioeconomic gradients of hypertension suggest that hypertension may increasingly affect adults in the lowest socioeconomic groups as LMICs develop economically.